2005
DOI: 10.1007/s10344-005-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

The nature of hunting around the Western Corridor of Serengeti National Park, Tanzania

Abstract: In many parts of Africa, illegal hunting is considered the most pressing issue in protected areas. Poaching has remained a persistent problem through the 50 year long history of Serengeti National Park. Around 2 million people live along the borders of the park. Poverty is widespread, and the population is increasing rapidly. In this paper we examine the local perceptions of importance and reasons for hunting, gender differences and opinions about mitigating measures among villagers around Serengeti's Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 43 publications
2
57
0
2
Order By: Relevance
“…Many environmental studies in the Serengeti have demonstrated that where poverty is widespread, conservation can seldom excel (7,10,45). It is unlikely for people to accept a scenario where biodiversity conservation implies starvation.…”
Section: Adopt Livelihoods and Production Strategies That Are Ecologimentioning
confidence: 99%
“…Many environmental studies in the Serengeti have demonstrated that where poverty is widespread, conservation can seldom excel (7,10,45). It is unlikely for people to accept a scenario where biodiversity conservation implies starvation.…”
Section: Adopt Livelihoods and Production Strategies That Are Ecologimentioning
confidence: 99%
“…Attitudes, i.e., positive or negative individually based evaluations of an object or situation (Manfredo 2008), have been reported to be key predictors of behaviors associated with bushmeat and hunting. For example, there is evidence that attitudes concerning the role of sharing bushmeat in the fulfilment of social, cultural, and political needs are equally important in rural and urban areas (Wiessner 2002, Kaltenborn et al 2005, Patton 2005). Beliefs about the sustainability of bushmeat consumption also shape behavior (Lee et al 2009), which is why the topic is frequently the subject of conservation campaigns (Milner-Gulland and Bennett 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Park rangers who actively search for snares and signs of illegal hunting have identified buffalo carcasses in the field (Hilborn personal observation) and buffalo meat appears in villagers bushmeat diets (Ndibalema and Songorwa 2007). Illegal hunting remains a large threat to conservation efforts in the Serengeti (Holmern et al 2007;Kaltenborn et al 2005;Loibooki et al 2002) and, therefore, we determined whether illegal hunting was a contributing factor to the spatial differences in buffalo recovery.…”
Section: Introductionmentioning
confidence: 99%